The Effectiveness of Retail Government Bond Issuance Policy Through The Electronic System as an Instrument of State Budget Financing - Ita Yenny; Umanto Umanto (Return : Study of Management, Economic and Bussines, 2023)
Since 2006, the issuance of Indonesia’s retail government bonds, known as Surat Utang Negara (SUN) Ritel, has played an important role as an instrument in financing the budget deficit. This statement in line with the fluctuating budget deficit ratio due to the volatility in the global financial market, which necessitates the government’s adoption of effective, efficient, prudent, market-deepening, and innovative financing management strategies. With the advancement of digital technology, governance in financing management needs to adapt to the modernization of administrative system, among other changes, through an electronic system, spesifically the e-government platform. Consequently, the government has transitioned to issuing retail bonds online through an electronic system (e-Government Securities) within the domestic market. In light of this context, this study aims to analyze the effectiveness of the SUN Ritel issuance policy through an electronic system using the post positivism paradigm, employing interview data collection techniques and document studies. The authors utilize a theory for evaluating policy effectiveness based on five aspects: right policy, right implementation, right target, right environment, and right process. The results of the study demonstrate that the policy of issuing SUN Ritel electronically is conducted in an accountable and transparent manner, providing more effective services. Eventually, this policy exhibits improved effectiveness across all five aspects of the right policy.